Academic use of WhatsApp, learning gains and perceived academic performance among IIUM undergraduate students : a descriptive study - Hamad, Hanadi (Kulliyyah of Education, International islamic University Malaysia, 2017)
This study explored the use of WhatsApp, a well-known smartphone application, among IIUM undergraduate students, and examined the relationships between its use and two dependent measures, i.e., students' perceived academic performance and learning gains. A convenience sample of 116 IIUM undergraduates completed an 18-item self-developed questionnaire measuring WhatsApp use, perceived academic performance, and learning gains on a 5-point response category ranging from Strongly Agree to Strongly Disagree. The results revealed that a majority of the respondents used WhatsApp for about two hours daily, mostly for chatting (85%) and communicating with classmates (81%). Some prevalent academic uses of WhatsApp were discussing assignments (89%), discussing course content (70%), and exchanging learning ideas (66%). While the given academic uses of WhatsApp were widespread among the undergraduates, only moderate numbers perceived learning gains and improved academic achievement resulting from their use of the application. The figures suggest the usefulness of WhatsApp for connecting learners and lecturers, but less so for meaningful academic learning. Consistent with the descriptive results, a moderate positive relationship was found between undergraduates' academic use of WhatsApp and learning gains (r = .428), as well as with their perceived academic performance (r = .412). The results highlight the role that WhatsApp might play to improve the interaction and communication between students and faculty, in addition to facilitating the learning of simple, not too complex educational content.